معوقات توظيف الإدارة الإلكترونية في إدارة خدمات الإرشاد الزراعي - د. آمنة مصطفى علي لطيف (Aljameai, 2025)
المستخلص:  تهدف الدراسة  لمعرفة أهم معوقات توظيف الإدارة الإلكترونية في ادارة خدمات الإرشاد الزراعي من وجهة نظر العاملين بها، والمتمثلة في المعوقات (الإدارية ، التقنية ، البشرية، المالية) والتعرف على آلية التغلب عليها، استخدم الباحث في هذه الدراسة المنهج الوصفي التحليلي وتَمثل مجتمع الدراسة في العاملين في إدارة خدمات الإرشاد الزراعي في كل من (وزارة الزراعة، جامعة طرابلس، جامعة الجفارة) باختيار عينة عشوائية من المدراء والموظفين و كل من لهم علاقة بموضوع الدراسة، و تم تجميع البيانات باستخدام استمارة استبيان أعدت لهذا الغرض وتم توزيع (120) استبانة، واسترجاع (95) استبانة مكتملة البيانات وصالحة للتحليل وبنسبة استرجاع بلغت (87%) وهي نسبة جيدة، واستخدمت مجموعة البرامج الإحصائية للعلوم الاجتماعية (SPSS) في تحليل البيانات، وخلصت الدراسة لعدة نتائج أهمها: إن توظيف الإدارة الالكترونية مازال يواجه العديد من المعوقات الإدارية التــي تؤخر عمليــة توظيف الإدارة الإلكترونية في إدارة خدمات الإرشاد الزراعي، كذلك قلة الدعم المادي والمعنوي، و ضعف البنية التحتية اللازمة لتوظيف الادارة الإلكترونية في إدارة خدمات الإرشاد الزراعي، وأيضاً ضعف الاستراتيجيات اللازمة لتأهيل وتدريب العاملين لغرض تطوير مهاراتهم وخبراتهم حتى يتم توظيف الإدارة الإلكترونية في إدارة خدمات الإرشاد الزراعي.Abstract: The study aims to identify the most important obstacles to employing electronic management in the management of agricultural extension services from the point of view of its employees, represented by obstacles (administrative, technical, human, financial) and to identify the mechanism for overcoming them. The researcher used the descriptive analytical approach in this study, and the study community was represented by employees in the management of agricultural extension services in each of (Ministry of Agriculture, Tripoli University, Al-Jafara University) by selecting a random sample of managers and employees and everyone related to the subject of the study. The data was collected using a questionnaire prepared for this purpose, and (120) questionnaires were distributed, and (95) questionnaires were retrieved with complete data and valid for analysis, with a recovery rate of (87%), which is a good rate. The Statistical Package for Social Sciences (SPSS) was used to analyze the data. The study concluded with several results, the most important of which are: employing electronic management still faces many administrative obstacles that delay the process of employing electronic management in the management of agricultural extension services, as well as the lack of material and moral support, the weakness of the infrastructure necessary to employ electronic management in the management of agricultural extension services, and also the weakness of the strategies necessary to qualify and train Workers for the purpose of developing their skills and experiences so that electronic management can be employed in the management of agricultural extension services.